From union catalogue to fusion catalogue: How collaborative cataloguing might be initiated and implemented in the Hong Kong context. Issue 1 (13th January 2014) - Cheung, Patti P.C.; Lau, Maria L.C.
Abstract : Purpose: – The purpose of this paper is to reflect The Chinese University of Hong Kong Library ' s catalogue evolution as a result of electronic resources cataloguing and how collaborative cataloguing could be implemented in the context of Hong Kong. Design/methodology/approach: – The paper outlines the challenges faced by The Chinese University of Hong Kong Library and the need to find alternative way to catalogue e-books come in large batches. It describes in particular the cataloguing of Chinese e-books in collaboration with the China Academic Library and Information System (CALIS). Findings: – Different cataloguing data set are inevitably blended into the library catalogue to be used by users. Still, collaboration is feasible when libraries are ready to make compromise and accept variances in the library catalogue. Originality/value: – The Chinese University of Hong Kong Library is the first library in Hong Kong to work collaboratively with CALIS to batch convert its records for cataloguing of Chinese e-books. The paper is useful for librarians exploring new source for Chinese cataloguing or collaborative initiatives with libraries in China.